2019
DOI: 10.1093/tropej/fmz062
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Early Onset Neonatal Sepsis among Neonates in Dodoma, Tanzania: A Case Control Study

Abstract: Objective To assess the predictors of early onset neonatal sepsis (EONS) among neonates in Dodoma Tanzania. Methods A hospital-based case-control study of randomly selected 105 cases and 217 controls in three hospitals in Dodoma region. Cases were neonates diagnosed with neonatal sepsis. Controls were matched to the cases by mother’s age and parity at a ratio of 1 case to 2 controls. A semi-structured questionnaire was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 22 publications
4
22
0
Order By: Relevance
“…Our study found that septic neonates more frequently had a Gram-negative source of infection (68% versus 37%, respectively) and were typically late-onset clinically, similar findings from developing countries have been reported [ 23 , 29 , 34 ]. These two findings suggest that infections are more frequently not vertically related from the mother, but rather horizontally transmitted from individuals responsible for the care of the baby, the hospital environment, or community-acquired [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our study found that septic neonates more frequently had a Gram-negative source of infection (68% versus 37%, respectively) and were typically late-onset clinically, similar findings from developing countries have been reported [ 23 , 29 , 34 ]. These two findings suggest that infections are more frequently not vertically related from the mother, but rather horizontally transmitted from individuals responsible for the care of the baby, the hospital environment, or community-acquired [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 89%
“…There was no significant association between demographic, perinatal, and clinical characteristics with unfavorable treatment outcomes among neonates with bacteriologically confirmed sepsis ( Table S5 ). In contrast, other studies have reported that preterm, low birth weight, late onset sepsis, home delivery, and Gram-negative sepsis were associated with unfavorable treatment outcomes [ 23 , 24 , 33 ]. These discordant findings may be due to the mixing of clinical factors from two different tertiary hospitals and other contextual variability.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Crude odds ratios (OR) and 95% confidence intervals (95% CI) were estimated for each exposure variable. Based on previous literature, we decided to include the following variables in our multivariable model; PROM, maternal fever in the last trimester and mode of delivery [27,28]. Other variables we included were birth weight, umbilical cord infection, prior antibiotic use, foul-smelling vaginal discharge, maternal age and education background.…”
Section: Discussionmentioning
confidence: 99%